In situ characterization of laser-induced strong field ionization phenomena - Noam Shlomo; Eugene Frumker (Light: Science & Applications)
Abstract Accurately characterizing the intensity and duration of strong-field femtosecond pulses within the interaction volume is crucial for attosecond science. However, this remains a major bottleneck, limiting accuracy of the strong-field, and in particular, high harmonic generation experiments. We present a novel scheme for the in situ measurement and control of spatially resolved strong-field femtosecond pulse intensity and duration within the interaction focal region. Our approach combines conjugate focal imaging with in situ ion measurements using gas densities pertinent to attosecond science experiments. Independent measurements in helium and argon, accompanied by a fitting to a strong-field ionization dynamic model, yield accurate and consistent results across a wide range of gas densities and underscores the significance of double ionization, as well as barrier suppression ionization. Direct spatially resolved characterization of the driving laser is a critical step towards resolving the averaging problem in the interaction volume, paving the way for more accurate and reliable attosecond experiments.